Little Bo-peep and friends - Parkin, Sarah (United Kingdom : Miles Kelly Publishing, Ltd., 2013)
This collection of best-loved nursery rhymes also includes fairytales and first poems. Children will love reading about Little Bo-peep, Goosey, Goosey Gander and Mary, Mary as they enjoy the beautiful illustrations.
Primary
Keywords: Children's poetry, English; Nursery rhymes, English; Fairy tales